2015
DOI: 10.1038/cr.2015.3
|View full text |Cite|
|
Sign up to set email alerts
|

Anticancer immunotherapy by CTLA-4 blockade: obligatory contribution of IL-2 receptors and negative prognostic impact of soluble CD25

Abstract: The cytotoxic T lymphocyte antigen-4 (CTLA-4)-blocking antibody ipilimumab induces immune-mediated longterm control of metastatic melanoma in a fraction of patients. Although ipilimumab undoubtedly exerts its therapeutic effects via immunostimulation, thus far clinically useful, immunologically relevant biomarkers that predict treatment efficiency have been elusive. Here, we show that neutralization of IL-2 or blocking the α and β subunits of the IL-2 receptor (CD25 and CD122, respectively) abolished the antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 60 publications
(79 reference statements)
4
111
0
2
Order By: Relevance
“…Recently, it has been reported that soluble CD25 (IL-2Ra) in baseline serum represented an independent indicator of OS for MM patients undergoing IPI therapy, highlighting the need to further investigate the role of soluble molecules as biomarkers for this therapy. 48 Notably, we could identify at baseline an inverse correlation between the absence of sNKG2DLs in the serum and the enrichment of few circulating T cell subsets (e.g., CD3 C CD4 C CD45RO C BTLA C , CD3 C CD4 C 4-1BB C , and Th17) in MM patients with clinical responses to IPI plus FTM regimen.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it has been reported that soluble CD25 (IL-2Ra) in baseline serum represented an independent indicator of OS for MM patients undergoing IPI therapy, highlighting the need to further investigate the role of soluble molecules as biomarkers for this therapy. 48 Notably, we could identify at baseline an inverse correlation between the absence of sNKG2DLs in the serum and the enrichment of few circulating T cell subsets (e.g., CD3 C CD4 C CD45RO C BTLA C , CD3 C CD4 C 4-1BB C , and Th17) in MM patients with clinical responses to IPI plus FTM regimen.…”
Section: Discussionmentioning
confidence: 94%
“…Elevated baseline soluble CD25 appeared to be associated with shorter OS, although the small number of patients precludes a definitive conclusion; however, in a larger series of patients treated with ipilimumab, baseline serum concentrations of sCD25 represented an independent indicator of OS, with high levels predicting resistance to therapy. 22 A mechanistic basis for this observation relates to findings that decoy sCD25 in mouse studies inhibits anti-tumor effects of CTLA4 blockade. 22 Thus, it appears that our findings regarding baseline sCD25 reflect the use of tremelimumab in the treatment schema (more likely than a relation to CD40 mAb) and indicates that baseline sCD25 as a negative predictor of survival following treatment with ipilimumab or tremelimumab may be a class effect.…”
Section: Discussionmentioning
confidence: 99%
“…22 A mechanistic basis for this observation relates to findings that decoy sCD25 in mouse studies inhibits anti-tumor effects of CTLA4 blockade. 22 Thus, it appears that our findings regarding baseline sCD25 reflect the use of tremelimumab in the treatment schema (more likely than a relation to CD40 mAb) and indicates that baseline sCD25 as a negative predictor of survival following treatment with ipilimumab or tremelimumab may be a class effect. Additional studies are needed to see if sCD25 may be a useful biomarker in patients with cancers other than melanoma and treated with CTLA-4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…We took advantage of two well-known immunogenic solid tumor models in mice, CT26 and MC38. These tumors are controlled by CD8 + T cells thus prone to respond to immunotherapy (14,17,22,23). Moreover, studies in mice have shown a link between mutational load of the tumor and clinical efficacy of immunotherapy (24).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor models, tumor inoculation in mice, and antitumor treatments CT26 and MC38 are two immunogenic tumor models controlled by CD8 + T cells and known to respond to immune checkpoint blockers such as anti-PD-1 (14)(15)(16)(17) Mouse single cell preparation from spleen, lymph node, lung, bone marrow, and tumors Spleen and lymph nodes. Single cells were obtained after mechanical disruption, and RBCs were lysed using ACK lysing buffer (spleen).…”
Section: In Vivo Bioactivity Of Rli In Micementioning
confidence: 99%